Water Mass Pathways to the North Atlantic Oxygen Minimum Zone - Llanillo, P (Blackwell Publishing Ltd, 2015)
The water mass pathways to the North Atlantic Oxygen Minimum Zone (naOMZ) are traditionally sketched within the cyclonic tropical circulation via the poleward branching from the eastward flowing jets that lie south of 10°N. However, our water mass analysis of historic hydrographic observations together with numerical Lagrangian experiments consistently reveal that the potential density level of σθ = 26.8 kg m-3 (σ26.8, approximately 300 m depth) separates two distinct regimes of circulation within the Central Water (CW) stratum of the naOMZ. In the upper CW (above σ26.8), and in agreement with previous studies, the supply of water mainly comes from the south with a predominant contribution of South Atlantic CW. In the lower CW (below σ26.8), where minimal oxygen content is found, the tropical pathway is instead drastically weakened in favor of a subtropical pathway. More than two thirds of the total water supply to this lower layer takes place north of 10°N, mainly via an eastward flow at 14°N and northern recirculations from the northern subtropical gyre. The existence of these northern jets explains the greater contribution of North Atlantic CW observed in the lower CW, making up to 50% of the water mass at the naOMZ core. The equatorward transfer of mass from the well-ventilated northern subtropical gyre emerges as an essential part of the ventilation of the naOMZ. © 2015. American Geophysical Union. All Rights Reserved.